Comparison of milk and plasma pharmacokinetics of meloxicam in postpartum versus mid‐lactation Holstein cows. Issue 3 (11th February 2018) - Gorden, P. J.; Burchard, M.; Ydstie, J. A.; Kleinhenz, M. D.; Wulf, L. W.; Rajewski, S. J.; Wang, C.; Gehring, R.; Mochel, J. P.; Coetzee, J. F.
Abstract : The objective of this study reported here was determine whether differences occurred in meloxicam pharmacokinetics between postpartum cows and mid‐lactation cows. Preliminary data from a separate study (P. J. Gorden, unpublished data) in postpartum cows demonstrated elevated plasma and milk concentration profiles compared to previously published data (Malreddy, Coetzee, KuKanich, & Gehring, 2013 ). Two different groups were enrolled, each with 10 cows. The treatment group (TRT) was postpartum cows treated with meloxicam, and the positive control (PC) group was cows in mid‐lactation treated with meloxicam. Plasma and milk meloxicam concentrations between the TRT and PC group were compared. Significant differences in meloxicam concentration in plasma were determined at all time points from 8 hr to 120 hr post‐treatment. In milk, there was a treatment ( p  =   .003), time ( p  <   .001), and treatment by time interaction ( p  <   .001). Significant differences in milk meloxicam concentration were determined at all time points from 8 hr to 96 hr post‐treatment, except for the 16‐hr time point. The time needed for meloxicam to no longer be detected in milk of the TRT group was longer compared to the PC group, indicating that a longer milk withdrawal is needed. These data suggest higher bioavailability as the underlying mechanism. Further research is needed to determine the mechanisms underlying differences this outcome.